Isolation of Heraclenin from Aegle marmelos correa and Screening for its Antimicrobial Activity Through in vitro & in silico Studies - P. Santhana Krishnan, V.; Karthikeyan, G.; Janaki, P.; Poonkodi, B.; Sathya, R. (Natural Products Journal, The, 2016)
Imperatorin, Heraclenin and Auraptene were isolated from the fruit pulp of Aegle marmelos correa. The structure of these compounds was confirmed by spectroscopic and single X-ray analysis. Among them Heraclenin crystallized out in large from the fruit pulp oil without further purification by conventional chromatographic techniques. The anti-microbial activity was performed on Xanthomonas oryzae pv. Oryzae and Colletotrichum lindemuthianum.
Keywords: Anti-microbial activity